Influence of Heat Treatment on the Corrosion Resistance of Aluminum-Copper Coating - Mieczyslaw Scendo; Slawomir Spadlo; Katarzyna Staszewska-Samson; Piotr Mlynarczyk (Metals, 2020)
Influence of heat treatment on the corrosion resistance of the aluminum-copper (Al-Cu) coating on the aluminum substrate was investigated. The coating was produced by the electrical discharge alloying (EDA) method. The surface and microstructure of the specimens were observed by a scanning electron microscope (SEM). The phase analysis of the composite materials by X-ray diffraction (XRD) and energy-dispersive spectroscopy (EDS) indicated that intermetallic compounds (i.e., CuAl2 and Cu9Al4) were formed through reactions between Al and Cu. during the EDA process. A significant increase in the hardness of the Al-Cu coating was affected by the improvement of the alloy structure. The heat treatment of materials was carried out at 400 °C or 600 °C in the air atmosphere. A corrosion test of materials was carried out by using electrochemical methods. The corrosive environment was acidic chloride solution. After heat treatment at 400 °C the mechanical properties of the Al/Cu alloy increased significantly and the oxide layer protect of the alloy surface against corrosion. However, after heat treatment at elevated temperature, i.e., 600 °C it was found that the (Al2O3)ads and (CuO)ads coatings were destroyed. The mechanical properties of the Al/Cu alloy decreased, and its surface has undergone deep electrochemical corrosion.